Posterior pole retinal detachment due to a macular hole in a patient with a Boston Keratoprosthesis - Daniel Gologorsky; Basil K. Williams, Jr.; Harry W. Flynn, Jr. (American Journal of Ophthalmology Case Reports, 2017)
Purpose: To describe the clinical course of a patient with a Boston Keratoprosthesis type I who developed a localized posterior pole retinal detachment secondary to a macular hole. Observations: A 73-year-old patient with a Boston Keratoprosthesis developed a localized posterior pole retinal detachment secondary to a macular hole. The retinal detachment was repaired with a 23-gauge pars plana vitrectomy, membrane peel, fluid-air exchange and 18% C3F8. Retinal reattachment was achieved but the macular hole remained open. Conclusions and importance: A posterior pole retinal detachment secondary to a macular hole can be repaired using standard techniques despite the limited view through a Boston Keratoprosthesis.